Maize production under ideal crop management conditions - Hashim Haneen Kareem / Khalil Abdulzahra Hasan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Yellow corn is one of the most important crops because it has a high nutritional value for humans and animals. In order to achieve this important nutritional value, it is necessary to follow the best ways in their cultivation to achieve high production and unique quality in terms of soil service, composting, irrigation, disease control, insects and attention to the harvest phase. All these things are essential in the development and prosperity of this strategic crop. The current study aims to highlight the best management methods for soil, crop service and pest control in order to raise farmers’ awareness of modern ways of growing maize crops as well as the simplified method of presenting the stages of agriculture and service in order to communicate information to peasants as well as those interested in agriculture.